The effect of different recovery methods on blood lactate removal in wrestlers - Ghorbani, S.; Mohebbi, H.; Safarimosavi, S.; Ghasemikaram, M. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: The first aim of this study was to compare the VO2 at lactate threshold (LT) and maximum rate of fat oxidation (Fatmax) intensity in wrestlers. A secondary aim was to compare the different recovery trials in wrestlers for finding effective methods of lactate removal post-match.